Some new Mathematical Properties for Kumaraswamy Fréchet distribution (Jurnal Matematika, Statistika dan Komputasi, 2022)
In this research, some mathematical properties for Kumaraswamy Fréchet distribution was presented, include entropy, the Shannon entropy, probability weighted moments, moments of residual life and mean of residual life. the properties were concluded for the Kumaraswamy Fréchet distribution using the probability density function (pdf) and cumulative distribution function according to linear representations.
Keywords: Probability weighted moments; entropy; Shannon entropy; moment of residual life; mean of residual life